Analisis Peran Koperasi Dalam Meningkatkan Kesejahteraan Anggotanya - Ryan Irwansyah Pasaribu; Kusmilawaty Kusmilawaty (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of the study was to analyze how the role of Civil Service Cooperatives Medan city government in improving the welfare of its members. This research is in the form of descriptive qualitative research. Researchers conducted observations, notes, and interviews during the data collection process. From the results of the study shows that the cooperative civil servants (KPN) Medan City Government has a very large role in the welfare of its members. The benefits include the provision of ease of Business Financing assistance services, educational scholarships for family members and the provision of training/workshops to improve the ability of human resources (HR). And also advised to cooperatives should cooperatives always improve and maintain the efforts that have been made in improving the welfare of members who are members and always make improvements to the efforts that the target has not been achieved. cooperatives always remain guided by the principles, foundations, principles, and goals of cooperatives in improving the welfare of cooperative members.